Training on Utilization of Local Plants as Medicine Family Alternatives in Naibonat Village - Indriati Andolita Tedju Hinga; Afrona EL. Takaeb; Sigit Purnawan (Dewan Pimpinan Daerah (DPD) Perkumpulan Dosen Indonesia Semesta (DIS) Jawa Timur, 2023)
Infectious diseases are still a public health problem in Indonesia, especially in Kupang Regency. Cases of infectious diseases in Kupang Regency are mostly suffered by the under-five age group. Limited access to health facilities, family economy and knowledge of parents causes children's health care to be less than optimal. Public health services cannot be evenly distributed without consider the existency of traditional medicine systems. Therefore, the solution offered from this program is to provide training on the use of local plants for health maintenance, disease prevention and treatment of minor illnesses or symptoms of disease that is carried out at home before going to health services. The target of this training is posyandu participants in Naibonat Village, Kupang Regency. The application of solutions includes counseling and training as well as assistance with practical methods and simulations regarding the introduction, processing and how to use local plants as alternative family medicine. The results obtained were an increase in the knowledge and skills of posyandu participants in utilizing local plants as an economical alternative medicine for families, especially for toddlers.